Urban agglomeration of Krasnodar: development and management - T. G. Lavrova (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The article discusses the main features of urban agglomeration and analyzes how the southern capital - the city of Krasnodar is able to become the core of the agglomeration to promote the development of neighboring territories. The author identifies prerequisites for the formation of Krasnodar city agglomeration based on the market flow of labor, goods and capital, social and cultural relations of the city with suburbs and nearby rural areas. The article defines the basic management steps and appropriate measures of purposeful work on creation in the Krasnodar urban agglomeration in contrast to the spontaneously emerging processes that increase the burden on the city and weakening the periphery.